The emergence of a new religious travel segment: Umrah do it yourself travellers (DIY) - Siti Atikah, Rusli *; Tan, Ai Ling *; Trupp, Alexander *; Chong, Daniel Ka Leong *; Arni, Abdul Gani; Vijaya Malar, V. A. * (University of Oradea, Romania and Gdansk University of Physical Education and Sport, Poland, 2022)
This research examines the rise of a new religious travel segment – the Umrah Do It Yourself (DIY) travellers. While Hajj is the fifth pillar of Islam, Umrah is a minor Muslim pilgrimage that can be undertaken at any time of the year, while still playing a crucial role in the completion of Hajj rituals. In the past, Umrah was managed by an authorised travel agent, who makes all the necessary pilgrimage preparations, from flights to trip itineraries. Recent years have seen an upsurge in travellers who prefer not to utilise the services of such agencies, but instead, to make their own arrangements. The decision by the Saudi Arabian government to launch a Tourist e-Visa in September 2019 has opened a window of opportunity for the legalization of Umrah DIY journeys. The objectives of this study are (i) to explore the travel motives that contribute to the success of the Umrah DIY, and (ii) to explore the factors that support and facilitate the decision for the Umrah DIY. The data were obtained via 20 semi-structured interviews with Umrah DIY travellers. The findings show that flexibility, spirituality, and budget have a crucial impact on travel motivation. Additionally, the findings suggest that information sources, travel quality, companionship/new friendship, and familiarity facilitate the choice of Umrah DIY travel. This research contributes to the growing scholarship on the Muslim travel market beyond Hajj and to studies on independent religious travel. Findings provide an opportunity for suppliers and industry participants to understand the travel motives of this new segment as a basis for producing relevant religious tourism products and services.